Analysis Of The Effect Of Addition Of Noni Fruit (Morinda citrifolia L.) In Used Fried Oil To Iodium Number - Sugito, Sugito; Firmansyah, Andi; Triana, Linda (poltekkes kemenkes pontianak, 2020)
Cooking oil is a food that is often used by the functioning community as a conductor of heat, a savory flavor enhancer and an increase in the calorie value of food. Some people use cooking oil with multiple uses as a medium for frying, the use of repeated cooking oil causes cooking oil to be used and if consumed it will be dangerous for health. Noni fruit (Morinda citrifolia L) is one of the fruits used as refining cooking oil its function as an adsorbent and chelating where its compounds have the ability to prevent damage and stabilize free radicals. The purpose of this study was to determine the effect of adding noni fruit to used cooking oil to iodine numbers. This research method is quasi-experimental. The sampling technique is purposive sampling. The sample used is cooking oil which is used to fry tilapia fish 4 times. This research was carried out by adsorption process that is by adding samples with noni fruit concentration concentration of 15%, 20%, 25% and 30% at a speed of 100 rpm for 60 minutes at a temperature of 90Â° C. Determination of iodine numbers is done by iodometric titration how the wijs work. Based on the results of the research that has been done, it can be seen that the magnitude of the values maintained by iod numbers with concentrations of 15%, 20%, 25% and 30% respectively are 48.10 Gram lod / 100 Gr. 49.43 Gram lod / 100 Gr. 50.71 Gram lod / 100 Gr and 51.47 Gram lod / 100 Gr. The results of the analysis of thetest were Linear Regression obtained (p= 0,000 <0.05), indicating that H0 is rejected and Ha is accepted, which mean where is the effect of adding noni fruit powder to iodine numbers.